2008
DOI: 10.1039/b718192b
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic activity of bimetallic platinum–gold catalysts fabricated based on nanoporous gold

Abstract: A tiny amount of Pt was deposited in a quasi-two-dimensional form onto the nanoporous gold (NPG) substrate through a simple immersion-electrodeposition (IE) method, forming nanostructured bimetallic Pt-Au catalysts. Such Pt-Au nanostructures have much higher structural stability than the bare NPG; moreover, they exhibit better catalytic activity and stronger poison resistance than commercial Pt-Ru catalysts because of the synergistic effect of the bimetallic compositions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 40 publications
2
67
0
1
Order By: Relevance
“…Bimetallic Pt-Au clusters have a wide range of catalytic applications, including oxygen reduction in fuel cells (Hernández-Fernández et al 2007), methanol and formic acid oxidations (Zhang et al 2008;Peng & Yang 2009) and selective oxidations (Bond et al 2006). In the bulk Pt/Au system, there is a miscibility gap at low temperature where Pt and Au are immiscible and Au prefers to segregate to the surface because of its lower surface energy (Okamoto & Massalski 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic Pt-Au clusters have a wide range of catalytic applications, including oxygen reduction in fuel cells (Hernández-Fernández et al 2007), methanol and formic acid oxidations (Zhang et al 2008;Peng & Yang 2009) and selective oxidations (Bond et al 2006). In the bulk Pt/Au system, there is a miscibility gap at low temperature where Pt and Au are immiscible and Au prefers to segregate to the surface because of its lower surface energy (Okamoto & Massalski 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanoporous gold (NPG) made by selective dissolution of silver from Au-Ag alloys under free corrosion conditions has attracted considerable interest [14][15][16]. Due to its unique structural properties, such as open bicontinuous metal-void phase, high surface-to-volume ratio and tunable porosity, NPG is more suitable for acting as the anode catalyst for electrooxidation of small organic molecules than bulk Au or Au nanoparticles [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, these results were not that remarkable while comparing with the effects over NPG catalysts, which was probably because most of the alkaline was adsorbed on the support C. Based on the experimental results above and those reported previously, it was confirmed that sodium hydroxide and ammonia played a decisive role in promoting the catalytic activity of NPG for the CO oxidation. The role of NaOH and ammonia is to provide OH -anions to form Au-OH -sites [32][33][34] to react with the introduced CO to form the reaction intermediate hydroxyl carbonyl (-OCOH -), which might also offer the assistance with -OH -to activate the oxygen. The probable reaction model is depicted as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the experimental and theoretical researches [28,31] from Mullins, Henkelman et al reported that the reaction rate of CO oxidation on atomic oxygen precovered Au(111) increased sharply with the presence of water. In alkaline reaction conditions, gold always exhibits a much higher catalytic activity than it is taken in acidic conditions, because of the formation of hydroxyl ions adlayers (Au À OH À ads ) on the gold surface [32][33][34]. Except for gold nanoparticles and nanotubes, nanoporous gold (NPG) has exhibited high activity for CO oxidation at low temperatures [35][36][37].…”
Section: Introductionmentioning
confidence: 99%